Bibliometric Analysis using Vos Viewer with Publish or Perish of Intelligent Tutoring System in Private Universities - Kurniawan, Bobi; Meyliana, M; Leslie Hendric Spits Warnars, Harco; Suharjo, Bambang; Ahiase, Godwin (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
The objective of this study is to analyze the development of intelligent tutoring systems in private universities. We conducted the analysis using bibliometric methods, utilizing the Publish or Perish and VOSviewer applications. Data was obtained by using the publish or perish application with the keyword "intelligent tutoring system in private university" from the Google Scholar database from 2019 to 2024. According to search results, the number of research papers has decreased from 117 to 23 from 2020 to 2024. Mapping using VOSviewer application produces three types of visualization, namely network, overlay, and density visualization. In its conclusion, this research notes a decrease in the number of studies discussing in private universities since 2020, but still shows great potential for development by other researchers.